Gerakan PHBS Rumah Tangga: Upaya Peningkatan Kesehatan Masyarakat di Nagari Rawang Gunung Malelo Surantih Sutera - Novia Zulfa Hanum; Adhyka, Nurmaines; Huvaid, Sevilla Ukhtil; Hidayat, Hilda; Arikhman, Nova (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Background: Clean and Healthy Lifestyle (PHBS) is one of the key promotive and preventive strategies to improve community health status. However, many households in rural areas have not fully implemented PHBS practices. Objective: This community service program aimed to improve knowledge and practice of PHBS at the household level in Nagari Rawang Gunung Malelo, Surantih Sutera, Pesisir Selatan District, West Sumatra, Indonesia. Methods: The program was carried out through health education sessions using interactive lectures, discussions, and demonstrations of PHBS practices. Evaluation was conducted by comparing pre-test and post-test results administered before and after the intervention. Results: Findings indicated a significant increase in community understanding of PHBS. The percentage of participants categorized as highly understanding increased from 10% (pre-test) to 55% (post-test), while the not understanding category decreased from 20% to 0%. These results demonstrate that interactive methods and direct practice effectively enhanced community knowledge and awareness regarding PHBS implementation at the household level. Conclusion: Interactive health education through lectures, discussions, and demonstrations proved effective in improving community knowledge and attitudes toward PHBS in Nagari Rawang Gunung Malelo. Continuous efforts through health cadre assistance, regular monitoring, and support from local government are required to ensure the sustainability of PHBS practices in daily life.